2018
DOI: 10.1039/c7py01167a
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic polypeptides bearing carboxybetaine and sulfobetaine: synthesis, self-assembly, and their interactions with proteins

Abstract: Zwitterionic polypeptides bearing carboxybetaine and sulfobetaine were synthesized and their self-assembly and protein interactions were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The results suggested all the hydrogel samples self-assembled to form ill-defined three-dimensional (3D) nano-assemblies. In the sol state, all the samples except 3 s -PLL 22 - b -PLeu 5.5 formed two-dimensional (2D) nano-assemblies [ 47 , 48 ]. Rather, 3 s -PLL 22 - b -PLeu 5.5 self-assembled to form one-dimensional (1D) fibrillar morphology, analogous to the study by Pine et al, showing that of the linear PLL- b -PLeu polypeptide hydrogels comprised of 1D twisted fibrils [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested all the hydrogel samples self-assembled to form ill-defined three-dimensional (3D) nano-assemblies. In the sol state, all the samples except 3 s -PLL 22 - b -PLeu 5.5 formed two-dimensional (2D) nano-assemblies [ 47 , 48 ]. Rather, 3 s -PLL 22 - b -PLeu 5.5 self-assembled to form one-dimensional (1D) fibrillar morphology, analogous to the study by Pine et al, showing that of the linear PLL- b -PLeu polypeptide hydrogels comprised of 1D twisted fibrils [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the neutral polymers, proteins bind electrostatically to charged polyelectrolytes. Such complexes have been used to stabilize proteins against aggregation, denaturation, or biochemical degradation. A limited number of studies of poly­(zwitterion) interactions with proteins reported that poly­(zwitterions) can inhibit antibody binding or substrate recognition, suggesting a direct protein–polymer association . In other studies, the polymers reportedly repel proteins such as BSA or lysozyme . Tethered zwitterionic chains also reportedly stabilize proteins. , These seemingly contradictory findings highlight the need for quantitative methods to establish the effect of poly­(zwitterions) on protein stability and thermal denaturation.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembled nanostructures of the polypeptide hydrogels (8.0 wt%) were characterized by small-angle X-ray scattering (SAXS) analysis ( Figure 4 ). For all hydrogel samples, the scattering intensity ( I ) exhibited a relation of I ( q ) ∝ q −n with n = 3.2–3.8, indicating the network forming 3D assembled nanostructures with ill-defined morphology [ 38 , 39 ]. The SAXS data were fitted by SasView software to compute the radius of gyration (R g ) of nano-assemblies formed by the packing of the grafted moieties.…”
Section: Resultsmentioning
confidence: 99%